Electroretinography - An Evolving Technique for Early Detection of Retinal Dysfunction - Muhammad Bilal, Maria Shahzadi, Muhammad Sikander Ghayas Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Human vision comprises different structures whose physiological functions act as variable for a healthy human vision. Retina plays a vital role in vision, in hosting different cells and neuron in ten layers. The perikaryal of these neurons are segregated from neurological processes, forming discrete layers1. The inner retina includes ganglion cells and amacrine cells, whereas the outer retina includes the rod and cone photoreceptors. The primary role of photoreceptors is to convert light energy into an electrical signal (phototransduction)2. The photoreceptors transmit visual information to second-order neurons known as bipolar cells in the middle retina. Rods synapse only with depolarizing bipolar cells, while cones synapse with both depolarizing and hyperpolarizing bipolar cells3. Electrophysiological responses from these cells can be recorded for testing of different diseases by using a technique known as “Electroretinography (ERG)”. This editorial explains how ERG can be used for testing dysfunctions, dystrophies, and the early detection of glaucoma.